Impact of diabetes mellitus and hemoglobin A1c level on outcomes among Chinese patients with acute coronary syndrome. Issue 7 (19th May 2020) - Xiong, Ran; He, Liu; Du, Xin; Dong, Jian‐Zeng; Ma, Chang‐Sheng
Abstract: Background: The impact of different glycemic control conditions on in‐hospital and long‐term outcomes among patients with acute coronary syndrome (ACS) is less well defined. Hypothesis: Diabetes mellitus (DM) with different admission hemoglobin A1c (HbA1c) levels (different glycemic control) could affect outcomes among Chinese patients hospitalized as ACS. Methods: We categorized 8961 Chinese ACS patients into one of the following three groups: "no DM" (group 1, n = 3773; no DM history and admission HbA1c < 6.5%), "DM with optimal control"(group 2, n = 2241; DM with admission HbA1c < 7.0%), "DM with suboptimal control"(group 3, n = 2947; DM with admission HbA1c ≥ 7.0%). The primary outcome was in‐hospital major adverse cardiovascular events (MACEs). 6098 patients were followed for a median of 3.85 years. Adjusted associations of these three groups with in‐hospital MACEs and long‐term mortality were determined. Results: DM with suboptimal control (group 3) was associated with greater in‐hospital MACEs (OR 1.46, 95% CI 1.17‐1.81, P = .001) than "no DM" (group 1). DM patients (group 2 and group 3) also had higher in‐hospital MACEs (OR 1.42, 95% CI 1.16‐1.73, P = .001) than "no DM" patients (group 1). It showed no significantly different in‐hospital MACEs between optimal (group 2) and suboptimal (group 3) control group (OR 1.06, 95% CI 0.84‐1.34, P = .63). Both optimal control (group 2) and suboptimal control (group 3) had a higher long‐term mortality (HR 1.26, 95% CI 1.02‐1.56, P = .03; HR 1.42, 95% CI 1.16‐1.73, P = .001). Conclusions: ACS patients with DM were associated with higher in‐hospital MACEs and long‐term mortality. Moreover, lower HbA1c level seems to have limited impact on cardiovascular events and long‐term mortality in this high‐risk population.